Assessment of borehole water quality in Nwadzekudzeku village, Giyani, Limpopo Province, South Africa: Implication for potential human health risks - Tsakane Patience Maluleke; Sifelani Dube; Emmanuel Daanoba Sunkari; Abayneh Ataro Ambushe (Journal of Trace Elements and Minerals)
Introduction: Due to a lack of potable water supplies in rural areas of South Africa, most rural communities depend on groundwater for subsistence. Concerns have been raised about the quality of Nwadzekudzeku village borehole water. Methods: This study investigated physicochemical parameters, anions and potentially toxic elements (PTEs) in drinking water to evaluate the borehole water quality from Nwadzekudzeku village. A multi-methods approach involving water quality analysis, geospatial mapping, multivariate statistical analysis, and human health risk analysis were employed in this study. Results and Discussion: The results showed that borehole water had a pH ranging from 6.96 - 7.76, an electrical conductivity (EC) of 132 - 2740 µS.cm−1, total dissolved solids (TDS) of 381 - 1336 mg.L−1, resistivity in the range of 62 - 1030 Ω, salinity from 0.32 - 1.34 ppt and an oxidation–reduction potential (ORP) of 9.20 - 233 mV. Most borehole water samples were found to have all physicochemical parameters above the maximum permissible levels (MPLs) set by the World Health Organization (WHO) and South African National Standards (SANS) except for pH and temperature. Concentrations of anions were determined in the mg.L−1 range with Cl− (44.0 – 853 mg.L−1) and NO3− (25.0 – 127 mg.L−1) as the only anions above WHO and SANS stipulated limits for drinking water. The results of cations showed that Na is the dominant cation with concentrations ranging from 42.8 – 241 mg.L−1, which exceed the WHO MPL. Based on the cation and anion dominance in the borehole water, the water is predominantly Na-Cl water type. The concentrations of PTEs in water were within the MPLs set by WHO. Multivariate statistical analysis revealed that the hydrochemical parameters were enriched in the aquifer through ion exchange reaction, dissolution of silicate minerals from the mafic-ultramafic lithologies, and agricultural activities. Children are the hypersensitive population with respect to nitrate toxicity in water as they show cumulative hazard index (HI) values ranging from 0.02 - 6.59 with an average value of 2.49, whereas HI for adults ranged from 0.02 - 4.71 with an average value of 1.78. Conclusion: This suggests that there is a high non-carcinogenic risk in the Nwadzekudzeku village because of the concentration of nitrate, as indicated by the average cumulative HI for children and adults being higher than the recommended value of 1.